The first genome-wide association study of internet addiction; Revealed substantial shared risk factors with neurodevelopmental psychiatric disorders - Haghighatfard, Arvin; Ghaderi, Amir Hossein; Mostajabi, Parmida; Kashfi, Seyedeh Sara; Mohabati somehsarayee, Hediyeh; Shahrani, Maryam; Mehrasa, Mahla; Haghighat, Saba; Farhadi, Mahdi; Momayez sefat, Maryam; Shiryazdi, Atena alsadat; Ezzati, Naghmeh; et al. (Research in developmental disabilities, 2023)
Internet addiction disorder (IAD) is listed as a disorder requiring further studies in the diagnostic and statistical manual of mental disorders (DSM-V). Psychological studies showed significant co-morbidity of IAD with depression, alcohol abuse, and anxiety disorder. Etiology and genetic bases of IAD are unclear. Present study aimed to investigate the genetic, psychological, and cognitive bases of a tendency to internet addiction. DNA was extracted from blood samples of IADs (N = 16,520) and 18,000 matched non-psychiatric subjects. Genotyping for the subjects was performed using SNP Array. Psychological, neuropsychological, and neurological characteristics were conducted. Seventy-two SNPs in 24 genes have been detected significantly associated with IAD. Most of these SNPs were risk factors for psychiatric disorders. Most similarity detected with autism spectrum disorder, bipolar disorder and schizophrenia. Higher anxiety, stress, and neuroticism and deficits in working memory, attention, planning, and processing speed were detected in IADs. This study is the first genome-wide association study of IAD that showed strong shared genetic bases with neurodevelopmental disabilities and psychiatric disorders. Genetic risk factors in IADs may cause several cognitive and neurodevelopmental brain function abnormalities, which lead to excessive Internet usage. It may suggest that IAD could be a marker for vulnerability to developmental psychiatric disorders. •There are genetic risk factors of Internet addiction disorder (IAD).•72 single nucleotide polymorphisms associated with IAD.•These genetic variants were risk factors of neurodevelopmental psychiatric disorders.•Hyper-geometricshowedsimilarity between IAD with ASD, BPD, SCZ and ADHD.•IADs showed higher anxiety, stress & neuroticism and memory, attention, planning & processing speed problems.